Development of interactive multimedia based on Lectora Inspire in chemistry subject in junior high school or madrasah tsanawiyah - Herdini Herdini; Roza Linda; Abdullah Abdullah; Nur Shafiani; Fitri ‘Alaina Darmizah; Praslita Dishadewi (Journal of Educational Sciences, 2018)
The research aims to develop interactive multimedia based Lectora Inspire on science chemistry subjects for SMP/MTs. The research method using the design of research and development (Research and Development) with a model Plomp, which consists of four phases; initial investigation, design, realization and construction, and validation, test and revision. The research was conducted at the University of Riau FKIP. The object of research is interactive multimedia Lectora Inspire. Data collected by validating based interactive multimedia Lectora Inspire to 3 validator (media expert and subject matter experts) and limited trial by users that teachers and students in SMP 4 and SMP Babussalam Pekanbaru. The results showed an average score of validator 98.20% . Score of limited trial based on questionnaire responses of teachers and students each obtained an average score of 98.78% and 97.03%. From the result of the average score of the validation and limited trial of interactive multimedia based Lectora Inspire for chemistry subjects for SMP / MTs valid and can be used as a learning media.